Double diapering facilitates hip maturation in newborns - Wei Chun Lee; Hsuan Kai Kao; Mei Chun Chen; Wen E Yang; Shih Ming Chu; Chia Hsieh Chang (Elsevier, 2022)
Background: Double diapering may help to maintain a baby's hips in flexion and abduction posture, but the efficacy in facilitating hip maturation has never been verified. We investigated whether double diapering results in greater improvement of the alpha angle in newborn babies. Methods: This prospective study enrolled newborns with Graf type IIa immature hips and assigned them to the double-diaper or single-diaper group by the day of birth in a week. Parents were instructed on proper hip positioning, except for diapering. Change in the alpha angle from newborn to 1 month after birth, rate of improvement to bilateral Graf type I hips in 1 month, and number of ultrasound examinations and orthopaedic clinic visits in the first year were compared between the two groups. Results: Seventy newborns with 102 type IIa hips were included from January to December 2017. They were allocated to the double-diaper group (n = 33) and single-diaper group (n = 37). With a comparable sex ratio, gestational age, and newborn alpha angle, the double-diaper group had a greater increase of alpha angles in 1 month than the single-diaper group (+7.9° vs. +5.2°, t-test, p = 0.011). Twenty-eight babies in the double-diaper group (84.8%) and 20 babies in the single-diaper group (54.1%) improved to having bilateral Graf type I hips (chi-square test, p = 0.006). Under the same clinical management pathway, subsequent clinical visits and hip ultrasounds before 1 year were significantly reduced in the double-diaper group. Conclusion: Double diapering enhances hip maturation and reduces clinical costs in newborns with physiological immature hips, but the therapeutic role for hip dysplasia requires further study.